2005
DOI: 10.1021/ol0520525
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Nonlinear Optical Behavior of β-Unsubstituted mesomeso E-Vinylene-Linked Porphyrin Dimers

Abstract: [structure: see text] A vinylene-linked porphyrin dimer, with no substituents at the beta-positions, has been synthesized by CuI/CsF promoted Stille coupling. In the crystal structure of this dimer, the C(2)H(2) bridge is twisted by 45 degrees relative to the plane of the porphyrins. The absorption, emission spectra, and electrochemistry reveal substantial porphyrin-porphyrin pi-conjugation. The triplet excited-state absorption spectrum of this dimer makes it suitable for reverse saturable absorption at 710-90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 26 publications
3
97
0
2
Order By: Relevance
“…[50c ,d] As before, alkynyl substituted porphyrins [53b,118] and porphyrin dimers with conjugating bridges [83] have found interest in OL studies. Comprehensive data are available for a series of metal complexes of the symmetric porphyrin 27.…”
Section: Chcl 3 129mentioning
confidence: 98%
See 1 more Smart Citation
“…[50c ,d] As before, alkynyl substituted porphyrins [53b,118] and porphyrin dimers with conjugating bridges [83] have found interest in OL studies. Comprehensive data are available for a series of metal complexes of the symmetric porphyrin 27.…”
Section: Chcl 3 129mentioning
confidence: 98%
“…[119,66a] A typical example on porphyrin dimers are the recent studies performed by Anderson and co-workers on 75. [83] Several studies have addressed the changes incurred upon inclusion of chromophores into other materials. For Zn II TPP it was shown that its incorporation into polymer films does not change the nonlinear refraction compared to in solution but that the material exhibits better photostability.…”
Section: Chcl 3 129mentioning
confidence: 99%
“…The selection of bonding sites can be important. For example, a structure with vinylene-meso-bridged porphyrin dimers exhibits a large electronic interaction [51], in contrast to β- Figure 16. Schematic representation of dipole moment switching in a ferroelectric porphyrin polymer.…”
Section: Ethyne-bridged Multiporphyrinsmentioning
confidence: 99%
“…The selection of bonding sites can be important. For example, a structure with vinylene-meso-bridged porphyrin dimers exhibits a large electronic interaction [51], in contrast to β-bridged analogs, which allow twisting of the macrocycles out of conjugation. The vinylene-meso-bridged structure also shows a substantial non-linear optical effect.…”
Section: Ethyne-bridged Multiporphyrinsmentioning
confidence: 99%
“…meso-meso-Conjugated porphyrin dimer [27] and trimer [28] without a linker were synthesized using Suzuki coupling, the same approach was used for the synthesis of dimers with face-to-face organized porphyrin units attached to aromatic linkers, [29] as well as for a linear trimer. [30] Stille coupling was used for the synthesis of various porphyrin dimers, [31,32] especially for the derivatives with long polyene systems. [33] Heck and Sonogashira reactions are also widely employed for the synthesis of bisporphyrin compounds with different linkers including acetylenic fragments, [34] the latter approach was helpful in the synthesis of porphyrin trimers as well.…”
Section: Introductionmentioning
confidence: 99%